Antioxidant Activity of the Mosses Breutelia subdisticha, Leptodontium viticulosoides and Pylaisia falcata (2021)
Mosses are used by many cultures to treat different diseases, probably due to their bioactive compounds, some of which may have antioxidant activity. This research evaluated the antioxidant activity (AA) of the species Breutelia subdisticha (Hampe) A. Jaeger, Leptodontium viticulosoides (P. Beauv.) Wijk & Margad. and Pylaisia falcata Schimp., from dichloromethane and ethanolic extracts, using the 2,2-diphenyl-1-picrylhydracil (DPPH*) and 2,2´-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS*+) methods. Inhibitory concentration (IC50) and relative antioxidant activity (% AAR) were determined from the extracts obtained using the Soxhlet technique, with subsequent statistical analysis (ANOVA and Tukey's post-hoc). The ethanolic extracts exhibited higher antioxidant capacity than those of dichloromethane. By the DPPH* method the ethanolic extracts showed a relative antioxidant activity with respect to ascorbic acid for L. viticulosoides 3.06, B. subdisticha 177.00 and P. falcata 141.66. Using ABTS*+ method, ethanolic extracts showed a relative antioxidant activity with respect to ascorbic acid for L. viticulosoides 1.75, B. subdisticha 139.17 and P. falcata 120.22. In conclusion, L. viticulosoides exhibited the best antioxidant activity, therefore, we propose to continue with its research, in order to achieve a pharmacological application from a natural source.